2017
DOI: 10.1615/intjmedmushrooms.2017024504
|View full text |Cite
|
Sign up to set email alerts
|

Shiitake Culinary-Medicinal Mushroom, Lentinus edodes (Agaricomycetes): A Species with Antioxidant, Immunomodulatory, and Hepatoprotective Activities in Hypercholesterolemic Rats

Abstract: Lentinus edodes is a culinary-medicinal mushroom that has an established history of use in Asian therapies. The mushroom offers well-documented beneficial health effects such as antihypercholesterolemic, antitumor, and antibacterial activities. In this study, dried powder of L. edodes fruiting bodies was used to evaluate immunomodulatory, hepatoprotective, and antioxidant effects in hypercholesterolemic rats. Albino rats (n = 24) were divided into 3 groups: the control (CON) group, the hypercholesterolemia-onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 18 publications
0
26
0
Order By: Relevance
“…In recent decades, various natural plant extracts have exhibited significant antioxidant activity [1,2]. These extracts encompass significant amounts of different bioactive molecules used in various pharmaceutical industry products [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, various natural plant extracts have exhibited significant antioxidant activity [1,2]. These extracts encompass significant amounts of different bioactive molecules used in various pharmaceutical industry products [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies revealed that plants as well as mushrooms have the antioxidant abilities. 9,10 Acetylsalicylic acid (ASA) is a vital signal molecule concerned within the plants growing processes, flower's enlargement and plants defense mechanism. 11 The Exogenous application of aspirin enhanced the CO 2 assimilation rate plant and increased dry masses under drought stress.…”
Section: Introductionmentioning
confidence: 99%
“…[40,41] Particularly, probiotic and prebiotic supplementations in T2DM adults that reported increase in Bi dobacterium and Coprococcus counts also showed marked improvement in glucose and lipid homeostasis [42]. Besides, restoration of Bi dobacterium and Coprococcus spp., these supplements were also associated with alleviations of hyperglycemia, hyperlipidemia, and hepatic steatosis in mice fed with HFD [43,44].…”
Section: Discussionmentioning
confidence: 94%